Quantification anomalies in single pulse LA-ICP-MS analysis associated with laser fluence and beam size. Issue 23 (25th October 2022) - Jerše, Ana; Mervič, Kristina; van Elteren, Johannes Teun; Šelih, Vid Simon; Šala, Martin
Abstract : Laser ablation inductively coupled plasma mass spectrometry (LA-ICP-MS) has undergone major improvements in recent years which have led to reduction of the analysis time, higher spatial resolution, and better sensitivity. Abstract : Laser ablation inductively coupled plasma mass spectrometry (LA-ICP-MS) has undergone major improvements in recent years which have led to reduction of the analysis time, higher spatial resolution, and better sensitivity. However, quantification and accurate analysis remain one of the bottlenecks in LA-ICP-MS analysis and so far satisfactory calibration solutions are restricted to well-documented matrices and suitable internal standards. Additional uncertainties associated with laser fluence and beam size via various ablation cells and interfaces make quantification even more challenging. This work is focused on the influence of fluence, beam size and aerosol transport on quantification in single pulse LA-ICP-MS analysis via approaches based on pulse intensity, LA spot volumes, noise characteristics, etc . for different elements (As, Gd, La, Ni, Te and Zn), concentrations (between 10 and 1000 μg g −1 ), and matrices (gelatin standards and NIST SRM 612). The findings indicate that selection of the appropriate laser fluence, just above the ablation threshold, and beam size, depending on the interface of LA and ICP-MS, are critical for reliable quantification and should be properly adjusted to avoid excessive Poisson and Flicker noise, achieve maximum sensitivity, and prevent the formation of double peaks in single pulses.